Linear theory of beam-wave interaction in double-slot coupled cavity travelling wave tube - 何昉明 谢文球 罗积润 朱敏 郭炜 (Chinese physics B, 2016)
A three-dimensional model of the double-slot coupled cavity slow-wave structure （CCSWS） with a solid round elec- tron beam for the beam-wave interaction is presented. Based on the ＂cold＂ dispersion, the ＂hot＂ dispersion equation is derived with the Maxwell equations by using the variable separation method and the field-matching method. Through numerical calculations, the effects of the electron beam parameters and the staggered angle between adjacent walls on the linear gain are analyzed.